The dynamic relationship between structural change and CO2 emissions in Malaysia: a cointegrating approach - Ali, W. (Springer Verlag, 2017)
The current study investigates the dynamic relationship between structural changes, real GDP per capita, energy consumption, trade openness, population density, and carbon dioxide (CO2) emissions within the EKC framework over a period 1971–2013. The study used the autoregressive distributed lagged (ARDL) approach to investigate the long-run relationship between the selected variables. The study also employed the dynamic ordinary least squared (DOLS) technique to obtain the robust long-run estimates. Moreover, the causal relationship between the variables is explored using the VECM Granger causality test. Empirical results reveal a negative relationship between structural change and CO2 emissions in the long run. The results indicate a positive relationship between energy consumption, trade openness, and CO2 emissions. The study applied the turning point formula of Itkonen (2012) rather than the conventional formula of the turning point. The empirical estimates of the study do not support the presence of the EKC relationship between income and CO2 emissions. The Granger causality test indicates the presence of long-run bidirectional causality between energy consumption, structural change, and CO2 emissions in the long run. Economic growth, openness to trade, and population density unidirectionally cause CO2 emissions. These results suggest that the government should focus more on information-based services rather than energy-intensive manufacturing activities. The feedback relationship between energy consumption and CO2 emissions suggests that there is an ominous need to refurbish the energy-related policy reforms to ensure the installations of some energy-efficient modern technologies. © 2017, Springer-Verlag Berlin Heidelberg.